Seroprevalence of Helicobacter pylori in a population of 15 to 35 years old in Mashhad - Mahdieh Khoshakhlagh; Mohammadreza Tarahomi; Fatemeh Asgharian; Arghavan Kamali; Safoora Sa'd Abadi; Kimia Jafarpour; Samaneh Abolbashari; Mojtaba Meshkat; Aida Gholoobi (Iranian Journal of Microbiology)
Background and Objectives: Helicobacter pylori (H. pylori) is a bacterium involved in gastrointestinal disorders with a high prevalence in Iran. We have determined the seroprevalence of H. pylori in the young adult population of Mashhad city for the first time. Materials and Methods: We carried out a cross-sectional study on 933 individuals between the ages of 15 and 35 in Mashhad. The serum level of IgG, IgM, and IgA H. pylori antibodies was determined using enzyme linked immunosorbent assay (ELISA) method. Results: The average age of the participants including 290 (31.0%) male and 643 (68.9%) female cases was 25.47 ± 5.76. H. pylori IgG was seropositive in 365 (39.1%) of subjects. Occupation (p=0.002), body mass index (p=0.002), marital status (p<0.0001), and age (p<0.007) were meaningfully related to H. pylori IgG seropositivity. Other factors such as sex, educational attainment, history of chronic diseases, and smoking cigarette had no significant relationship with the presence of H. pylori antibodies. Conclusion: The seroprevalence of H. pylori IgG antibodies in Mashhad's 15 to 35 years old citizens was determined 39.1%. We suggest further studies with larger sample sizes and different age groups as the target population.